Disclose Tadlis Practice of Muslim Traders in Traditional Market - Syahputri, Eno Fitrah; Abdullah, Muhammad Wahyuddin; Haddade, Abdul Wahid; Arif, Widyantono (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This research has purpose to disclose tadlis practices of muslim traders in traditional market. This research uses qualitative descriptive research method with phenomenological approach. Data collecting method which used is observation, interview, and documentation. Research result finds there is qualitative and quantitative c practices in Sugguminasa market. Qualitative practices is shown by mixing good’s quality, hiding defective goods, dishonesty of good’s quality as well as manipulating good’s condition to make them look fresh and new. On tadlis quantity is shown by act of decreasing scale quality so it was occurred inconsistency between price and good’s quality. Meanwhile practical implication shall be ground for government in providing with tight supervisory and taking into account accuracy as well as scale tool standard as used by trader in order to achieve scale accuracy pursuant to Indonesian National Standard (SNI).